Screening and Identifying Immune-Related Cells and Genes in the Tumor Microenvironment of Bladder Urothelial Carcinoma: Based on TCGA Database and Bioinformatics - Cao, Jinlong; Yang, Xin; Li, Jianpeng; Wu, Hao; Li, Pan; Yao, Zhiqiang; Dong, Zhichun; Tian, Junqiang (Frontiers in Oncology, 2020)
Bladder cancer is the most common cancer of the urinary system and its treatment has scarcely progressed for nearly 30 years. Advances in checkpoint inhibitor research have seemingly provided a new approach for treatment. However, there have been issues predicting immunotherapeutic biomarkers and identifying new therapeutic targets. We downloaded the gene expression profile and clinical data of 408 cases bladder urinary cancer from the Cancer Genome Atlas (TCGA) portal, and the abundance ratio of immune cells for each sample was obtained via the “Cell Type Identification by Estimating Relative Subsets of RNA Transcripts (CIBERSORT)” algorithm. Then, four survival-related immune cells were obtained via Kaplan-Meier survival analysis, and 933 immune-related genes were obtained via a variance analysis. Enrichment, protein-protein interaction, and co-expression analyses were performed for these genes. Lastly, 4 survival-related immune cells and 24 hub genes were identified, four of which were related to overall survival. More importantly, these immune cells and genes were closely related to the clinical features. These cells and genes may have research value and clinical application in bladder cancer immunotherapy. Our study not only provides cell and gene targets for bladder cancer immunotherapy, but also provides new ideas for researchers to explore the immunotherapy of various tumours.